Development of Portfolio Assessment Tools through A Scientific Approach for the Advancement of Education - Kusumaningtyas, Dian Artha (Program Studi Pendidikan Fisika UHAMKA, 2018)
Assessment is an important component in the implementation of education. Efforts to improve the quality of education can be pursued through improving the quality of learning and the quality of the assessment system. Assessment must include cognitive, affective, and psychomotor aspects. This study aims to produce a portfolio with a scientific approach that can assess three aspects, namely cognitive, affective, and psychomotor aspects. Advancement of education needs to be thoroughly designed from the planning, implementation, and evaluation stages of learning. Assessment methods that are carried out include research and development using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Then, the product is validated by material expert lecturers, media experts, assessment experts, and teachers. The result of product feasibility testing in the form of portfolios are stated to be good and very good and it can be concluded that based on the expert validator's assessment, the product developed is stated to be suitable for use.